Physical activity motivations in individuals over 65 years of age participating in European Sports Week activities - Erbaş Ülfet; Gümüş Hüseyin; Karakullukçu Ömür Fatih (SHS Web of Conferences)
As the global population continues to age, there is a growing trend in the development of ageand health-specific adapted sports activities for older adults. Prior research indicated a surge in the demand for adapted sports activities among older individuals, and European Union (EU) countries have also been swift in implementing new policies in response to this growing demand. The European Week of Sports is a collaborative initiative of the Ministry of Youth and Sports and the Directorate for EU Affairs. It is celebrated concurrently in 81 provinces of Turkey with the motto #BeActive, which reflects the EU’s commitment to promoting physical activity among its citizens. The present study attempts to examine the motivational factors underlying the physical activity participation of individuals aged 65 years and older participating in the European Week of Sports activities. We administered the Motivation Scale for Physical Activity Participation, developed by Tekkurşun-Demir and Cicioğlu (2018), to 1,567 individuals, 605 females and 962 males, aged 65 years and older. In addition to descriptive statistics, we adopted inferential statistics independent samples t-test and one-way analysis of variance (ANOVA) to analyze the data. The findings indicated that participants’ physical activity motivation did not significantly differ by gender. However, participants’ respective motivational factors significantly differed by their body mass index values. We can assert that participants of the European Week of Sports exhibited high levels of motivation and positive perceptions of health. Besides, we found that the primary motive for physical activity engagement among our participants was individual (M = 4.15, SD = .41), followed by environmental (M = 3.78, SD = .77). Overall, we concluded that participants’ physical activity motivation was not affected by gender and that perceived health and income status emerged as the most significant parameters in physical activity motivation.